Spontaneous perforation of the bladder in a patient operated for a lung abscess: a case report - Velizar Hadzhiminev (International Journal of Surgery and Medicine, 2018)
We present a rare case of a spontaneous perforation of the bladder in a female patient who underwent thoracic operation. A 45 year-old female patient with no other comorbidities was admitted to the department of thoracic and abdominal surgery of University hospital “Sveti Georgi” with clinical, laboratory and image findings of right lung abscess. A right thoracotomy was performed, a large lung abscess was found and upper right bilobectomy was performed. On the day of her discharge she complained of a sudden abdominal pain, ballooning of the abdomen, nausea and vomiting. The ultrasonography showed a free fluid in the peritoneal cavity. An urgent laparotomy was performed, a perforation of the bladder was found, resection of the necrotic part of the wall and two layer suture of the bladder were performed by urologist. Postoperatively, we had multiple complications. Tuberculosis was considered as one of the most likely diagnosis but was subsequently rejected. The patient was discharged after 70 days of hospital stay in a good health condition.